2018
DOI: 10.1039/c7cc08920a
|View full text |Cite
|
Sign up to set email alerts
|

Copper/guanidine-catalyzed asymmetric alkynylation of isatin-derived ketimines

Abstract: Isatin-derived ketimines undergo enantioselective alkynylation reactions in the presence of copper iodide and easily accessible guanidine-amides. The corresponding 3-alkynyl-3-aminooxyindoles are obtained in up to 95% yield and 96% ee. The guanidine plays a role in the formation of copper acetylide and the enantiodetermining step and the basic additive is excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…The propargylic amine N-Boc derivative 3a was prepared by the reaction of isatinderived N-Boc ketimine and phenylethynylmagnesium bromide. 11 The reaction of 3a under the typical reaction condition (−15 C) did not produce spirooxindole 4a, and no reaction was also observed even at elevated temperature (50 C). The failure might be due to steric hindrance around the nitrogen atom and delocalization of the anion at nitrogen atom to oxygen atom of the Boc moiety.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The propargylic amine N-Boc derivative 3a was prepared by the reaction of isatinderived N-Boc ketimine and phenylethynylmagnesium bromide. 11 The reaction of 3a under the typical reaction condition (−15 C) did not produce spirooxindole 4a, and no reaction was also observed even at elevated temperature (50 C). The failure might be due to steric hindrance around the nitrogen atom and delocalization of the anion at nitrogen atom to oxygen atom of the Boc moiety.…”
Section: Resultsmentioning
confidence: 92%
“…As a last entry, we examined the synthesis of nitrogen analog 4 , as shown in Scheme 3. The propargylic amine N ‐Boc derivative 3a was prepared by the reaction of isatin‐derived N ‐Boc ketimine and phenylethynylmagnesium bromide 11 . The reaction of 3a under the typical reaction condition (−15 °C) did not produce spirooxindole 4a , and no reaction was also observed even at elevated temperature (50 °C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the role of copper salt and ligands in the 1,3‐dipolar cycloaddition of azides is not easily explained, we envisioned that if an appropriate chiral ligand is introduced into this copper catalyzed three‐component azide‐alkyne cycloaddition/[2+2] cascade reactions, it might allow an alternative enantioselective version by trapping a chiral ligand coordinated copper ketenimine species (Scheme b, right). Recently, our group and others have successfully explored chiral guanidine/CuI complexes in the asymmetric reactions, including C−H insertion of α‐diazoesters to terminal alkynes, and asymmetric alkynylation ,. Our study demonstrated that enantioselective trapping of allenoate‐ or acetylide copper(I) species are effective under chiral guanidine ligands.…”
Section: Methodsmentioning
confidence: 87%